Polymer insulator coated by room temperature vulcanization for strengthening voltage withstand capabilities - Jamaludin, Farah Adilah (2020)
Non-ceramic type insulator, also known as polymer insulator has become an alternative to most power utilities worldwide due to its advantages. However, polymer insulator has some major drawbacks such as its material properties that are easily degraded and aging that results in unknown long-term reliability. Typical problems encountered by the polymer insulator during its years of service have included tracking and erosion of the shed that could lead to flashover, and chalking that can increase contamination accumulation on the shed or housing, and bonding and electrical failures due to interference between different materials. All these typical problems were due to prolonged exposure to atmospheric pollution, ultra-violet radiation (UV), rain and salt fog. Furthermore, being a tropical country with high lightning intensity, 70% of power outages in Malaysia are caused by lightning. Lightning strikes overhead power lines, causing surge over voltages and that affect performance of polymer insulators and lead to flashover and damage to the insulator or power lines. Under normal circumstances, the damaged polymer insulator will be replaced with a new one but it is labour-intensive and costly. Alternatively, in this research, new method of use, which is applying Room Temperature Vulcanisation (RTV) coating on polymer insulator surfaces in order to increase electrical performance of the insulator and also to restore a damaged insulator without the need to shut down the power lines. Previously, RTV coating method was widely used in outdoor porcelain and glass insulators to enhance electrical performance under pollution condition and increase their life span. Since there are no past measurements available for the polymer insulator, this research offers three different types of insulator configuration settings used in this work, namely, basic uncoated, and RTV types 1 and 2 coated insulators. All the insulators were tested under dry, clean-wet and pollution conditions under alternating and different lightning impulse voltage conditions. From the research, RTV-coated insulator was found to increase polymer insulator withstand capabilities up to 50% under pollution condition and reduce leakage current magnitude. From the study, application of RTV coating was found to be effective for strengthening voltage withstand capabilities under alternating and lightning impulse voltages. RTV coating can be used to improve and protect the surface condition of the polymer insulator. This may help to improve the performance of the polymer insulator and increase its lifespan and power system reliability.